Iterative Preparation of Platinum Nanoparticles in an Amphiphilic Polymer Matrix: Regulation of Catalytic Activity in Hydrogenation - Osako, Takao; Srisa, Jakkrit; Torii, Kaoru; Hamasaka, Go; Uozumi, Yasuhiro (Synlett, 2020)
We demonstrate that iteration of the seeded preparation of platinum nanoparticles dispersed in an amphiphilic polystyrene–poly(ethylene glycol) resin (ARP–Pt) regulates their catalytic activity in the hydrogenation of aromatic compounds in water. The catalytic activity of the fifth generation of ARP–Pt [G5] prepared through four iterations of the seeded preparation was far superior to that of the initial ARP–Pt [G1] in the hydrogenation of aromatic compounds in water.
Keywords: iterative preparation; platinum catalysis; nanoparticles; hydrogenation; aromatic compounds